Women's status and qualitative perceptions of a cash assistance programme in Raqqa Governorate, Syria. Issue 2 (4th May 2019) - Blackwell, Alexandra; Casey, Jean; Habeeb, Rahmah; Annan, Jeannie; Falb, Kathryn
ABSTRACT: Cash and voucher assistance is an efficient way to deliver assistance in emergency settings, and evidence demonstrates that cash programmes have consistent positive impacts on food security and other health and economic outcomes in these contexts. Nevertheless, while evidence from development settings shows that cash has the potential to reduce intimate partner violence and increase empowerment for women and girls, there is a dearth of rigorous evidence from acute humanitarian settings. In response to this evidence gap, the International Rescue Committee conducted an evaluation of a cash programme in Raqqa Governorate, Syria. The aim was to examine the effect of a cash for basic needs programme on outcomes of violence against women, and women's empowerment. This article draws on qualitative data from interviews with 40 women at the end of the cash programme. It offers evidence of potential increased tension and abuse within both the community and the household for some women whose families received cash, as well as potential increased social protection through repayment of debts and economic independence for others. Both negative and positive effects could be seen. While the objective of the cash programme was not to influence underlying power dynamics, this research shows it is necessary to integrate gender-sensitive approaches into programme design and monitoring to reduce risk to women of diverse identities.